Chordomas: From Stem to Stern. (30th June 2022) - Freiburg, Luke; Demos, Terrence C.
Abstract : Although rare, chordomas can affect the entire axial skeleton, and they are the most common primary malignant bone tumor in both the sacrum and the spine. This article details tumor origin, epidemiology, pathology, and imaging features, in an effort to improve the ability of the radiologist to diagnose, provide a differential diagnosis, and further understand treatment of patients with chordomas.